Early Outcome of Open Versus Laparoscopic Cholecystectomy for Symptomatic Gallbladder Stone Disease in A Resource-Limited Setting: A Retrospective Review (Tanzania Medical Journal, 2021)
BackgorundGallbladder diseases requiring surgery are a common condition among general surgical practice. Cholecystectomy is thus commonly practiced/practice with laparoscopic cholecystectomy (LC) as the gold standard. Seven years now, LC has slowly developed at Muhimbili National Hospital (MNH) but proportional numbers of patients still receive open cholecystectomy. This study was therefore undertaken to assess and compare the outcomes of the two methods of surgical treatment in a resource-limited setting in order to provide evidence based data for informed change in surgical care of patients with symptomatic gallbladder stone disease. MethodsA retrospective chart review of patients who had cholecystectomy from February 2012 to February 2017 was carried out. Medical records in the operating room were searched and case notes retrieved. Information regarding demography, operative time, post-operative stay, complications, and mortality was extracted. Between groups comparison of variables was done using chi square test, where p value of greater than 0.05 indicated similarity between the two groups. An independent sample t test was used to compare the operative time, hospital stay and for post-operative complications. ResultsThis retrospective study reviewed 182 cases for the period of 6years. The patients undergone laparoscopic cholecystectomy or or open cholecystectomy. The hospital stay was significantly shorter in the LC group compared to open cholecystectomy (OC) group with mean hospital stay of 2.15± 1.165 days and 3.82±2.25 days respectively (p< 0.001). The mean operative time for LC was longer 109.78±40.38 minutes compared with patients in the OC group 79.78±27.23 minutes (p < 0.001). No significant differences were observed in complications and mortality between the two groups. ConclusionLC and OC are comparable procedures for the treatment of gallstone disease in terms of morbidity and mortality although LC had significantly shorter hospitals stay. However, the operative time was longer in LC group. At MNH, LC should be a procedure of choice and further study on cost-effectiveness of LC should be conducted. Key words: Gall stones, Laparascopy Gallstones, Laparoscopy Cholecystectom.